The Pārijāta Tree: A Giant Tree in the Heavenly Realm - Yang Gao (Religions)
Focusing on the Pārijāta Tree on the summit of Mount Sumeru, the centre of Asian cosmology, this study analyses its depictions and images. These include Chinese translations of Buddhist texts, the most notable depictions in the handscrolls from the Dūn Huáng and Harvard Art Museums, its representations in Japanese classical literature and early modern Japanese illustrations of Mount Sumeru. Finally, drawing from the discussions on trees in the Buddhist texts, A Forest of Pearls from the Dharma Garden [法苑珠林, Fǎ yuàn zhū lín], the study also addresses various issues surrounding tree felling, which are relevant to the current concerns of environmental protection. I argue that the Pārijāta Tree, positioned as the heavenly king of trees, holds significance as a core figure at the centre of the cosmos. The Pārijāta Tree can be said to serve as a metaphor for the supreme state pursued by Buddhist practitioners. Furthermore, this study suggests that issues related to Asian cosmology or worldviews should be pursued as important subjects in future research on environmental literature.